2018
DOI: 10.1186/s12889-018-6044-y
|View full text |Cite
|
Sign up to set email alerts
|

Establishing the international prevalence of self-reported child maltreatment: a systematic review by maltreatment type and gender

Abstract: BackgroundEstimating the prevalence of child maltreatment is challenging due to the absence of a clear ‘gold standard’ as to what constitutes maltreatment. This systematic review aims to review studies using self-report maltreatment to capture prevalence rates worldwide.MethodsPubMed, Ovid SP and grey literature from the NSPCC, UNICEF, The UK Government, and WHO from 2000 to 2017 were searched. The literature review focused on the variation found in self-reported lifetime prevalence for each type of maltreatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
173
4
11

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 281 publications
(223 citation statements)
references
References 55 publications
16
173
4
11
Order By: Relevance
“…Domestic violence is considered to be a threat to the existing system of values, a manifestation of breaking of the social norms and a symptom of social pathology on a national and global scale [14,15,16]. This vital issue has been within the scope of social and other studies in Poland for over 20 years, and interest in it is growing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Domestic violence is considered to be a threat to the existing system of values, a manifestation of breaking of the social norms and a symptom of social pathology on a national and global scale [14,15,16]. This vital issue has been within the scope of social and other studies in Poland for over 20 years, and interest in it is growing.…”
Section: Discussionmentioning
confidence: 99%
“…The victimization of children and adolescents, including domestic violence, was an important subject of the 2013 National diagnosis of the problem of violence against children [19]. The studies showed that 71% of teenagers aged [11][12][13][14][15][16][17] have experienced at least one form of violence in various situations, including the family environment.…”
Section: Discussionmentioning
confidence: 99%
“…(3,7) Child abuse, in particular neglect, is a big problem in low resource settings such as in Africa, especially in the under 5 population. (8)(9)(10)(11) This under 5 population is the age group with the highest incidence of poisoning. (1-3, 7, [12][13][14] In LMICs, neglect may present as accidental poisoning as children are often left unsupervised, while child abuse may present as intentional or occult poisoning.…”
Section: Introductionmentioning
confidence: 99%
“…apontaram que, somente no ano de 2011, o país registrou 39.281 atendimentos na faixa de 1 a 19 anos idade, que representam 40% do total de 98.115 atendimentos computados pelo sistema nesse ano. 1,3 A prevalência de declínio cognitivo na população mundial representa um verdadeiro problema de saúde pública, com uma incidência crescente a cada ano. Um dos fatores que também está relacionado ao aumento dessa prevalência é a constatação do envelhecimento populacional crescente, não somente no Brasil, mas em todo o mundo.…”
unclassified
“…Apesar de sua importância, estimar a prevalência de maus-tratos na infância é um desafio pela ausência de um "padrão ouro" claro sobre o que constitui maus-tratos. 3 No Brasil, as situações de maus-tratos infantis ganharam visibilidade no final da década de 1980, momento em que a Constituição Federal de 1988 e o Estatuto da Criança e do Adolescente (ECA) de 1990 passaram a exigir a notificação de casos suspeitos ou confirmados de violência infantil. A partir de então, as políticas de proteção à criança e ao adolescente começam a se firmar.…”
unclassified